Academia between Utopia and Dystopia: Francis Bacon, Ursula K. Le Guin, and Alasdair MacIntyre - Paweł Kaźmierczak (Ignatianum University Press, 2018)
The paper examines two visions of the relation between science and society through the utopian novel New Atlantis, by Bacon, and the dystopian novella, New Atlantis, by Le Guin. In Francis Bacon's classic utopia scientists enjoy high social status and have all imaginable resources at their disposal, whereas the contemporary Ursula K. Le Guin's dystopia portrays heroic scientists in a totalitarian state, subjected to imprisonment, torture and constant surveillance for practicing ethical science. Taking cue from these two texts I employ MacIntyre's framework of internal and external goods of a practice to discuss the relationship between the contemporary academia and the state. The internal goods of science (knowledge, "light", discoveries and inventions) are what scientists contribute to the society, whereas the external goods, such as material riches, prestige, power (or the opposite thereof) are what society supplies the scientists with. My conclusion is that values drawn from a religious tradition can help treat the external goods as means, and the internal goods as the actual ends of the academic practice.